Plasmodium falciparum merozoite surface protein 3 as a vaccine candidate: a brief review - Alves, Késsia Caroline Souza (2022)
Despite the many efforts of researchers around the world, there is currently no effective vaccine for malaria. Numerous studies have been developed to find vaccine antigens that are immunogenic and safe. Among antigen candidates, Plasmodium falciparum merozoite surface protein 3 (MSP3) has stood out in a number of these studies for its ability to induce a consistent and protective immune response, also being safe for use in humans. This review presents the main studies that explored MSP3 as a vaccine candidate over the last few decades. MSP3 formulations were tested in animals and humans and the most advanced candidate formulations are MSP3-LSP, a combination of MSP3 and LSP1, and GMZ2 (a vaccine based on the recombinant protein fusion GLURP and MSP3) which is currently being tested in phase II clinical studies. This brief review highlights the history and the main formulations of MSP3-based vaccines approaches against P. falciparum.